Questions improve oratory lawyers. (Journal of actual problems of jurisprudence, 2016)
In article author specified basic requirements pre-shown to part of advocate in process. Part of advocate must not only to influence on decision or on sentence of court, but and to have educator value for participating in process which must to realize himself responsibility and to make corresponding conclusions.In article author specified basic requirements pre-shown to part of advocate in process. Part of advocate must not only to influence on decision or on sentence of court, but and to have educator value for participating in process which must to realize himself responsibility and to make corresponding conclusions.
Keywords: advocate; advocatura; sudebnie prenie; obbinitelny resh prokurora; zashitelny htsh advocate